2009
DOI: 10.1590/s1519-38292009000300003
|View full text |Cite
|
Sign up to set email alerts
|

Condições de saúde bucal de crianças na faixa etária pré-escolar, residentes em áreas de abrangência do Programa Saúde da Família em Salvador, Bahia, Brasil

Abstract: Objectives: to determine the prevalence and severity of dental caries, malocclusions and gum damage in five-year-old preschool children resident in areas covered by the Family Health Program (PSF).Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
2
16

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 12 publications
3
12
2
16
Order By: Relevance
“…As for caries experience in the children in our study, we found a baseline prevalence of 16.53%, similar to the results published by Declerk et al 33 for Table 6 Crude and adjusted relative risks (RR) and respective 95% confi dence intervals (95%CI) for the association between maternal common mental disorders (CMD) and caries incidence in 3 teeth or more in preschoolers, according to daily brushing, based on robust Poisson regression. Salvador 12 ; in Salvador, Bahia, 50% of children at 5 years had at least one decayed deciduous tooth 13 . The influence of distal variables such as socioeconomic conditions on the development of early dental caries has been extensively researched, and this knowledge is now well-consolidated in the literature.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As for caries experience in the children in our study, we found a baseline prevalence of 16.53%, similar to the results published by Declerk et al 33 for Table 6 Crude and adjusted relative risks (RR) and respective 95% confi dence intervals (95%CI) for the association between maternal common mental disorders (CMD) and caries incidence in 3 teeth or more in preschoolers, according to daily brushing, based on robust Poisson regression. Salvador 12 ; in Salvador, Bahia, 50% of children at 5 years had at least one decayed deciduous tooth 13 . The influence of distal variables such as socioeconomic conditions on the development of early dental caries has been extensively researched, and this knowledge is now well-consolidated in the literature.…”
Section: Discussionmentioning
confidence: 97%
“…Early caries affects not only oral health, since compromised deciduous dentition increases the risk of caries in the permanent teeth, but also the child's physical, emotional, and cognitive development 11 . From the epidemiological perspective, caries was observed in 60% of Brazilian children at 5 years of age in 2004 12 , and in Salvador, only 50% of 5-year-old children were caries-free in 2005 13 .…”
Section: Introductionmentioning
confidence: 99%
“…This transformation would be possible through conceptual redefinition and reorientation of practices aimed at actions based on the principles of integrity, coordination, and continuity of care by the OHT, among other strategic actions 2 . Researchers have investigated the role of the OHT/FHS, particularly in aspects related to the micro-process work, innovation in care models, and potential epidemiological impact on oral health [3][4][5][6][7] . These studies' findings are important as they can influence future practices and investment in resources and serve as a basis for the development of other studies 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have investigated the role of the OHT/FHS, particularly in aspects related to the micro-process work, innovation in care models, and potential epidemiological impact on oral health [3][4][5][6][7] . These studies' findings are important as they can influence future practices and investment in resources and serve as a basis for the development of other studies 3,4 . Thus, this review and comment on the scientific literature concerning the oral health topic in FHS allows more insight into the working process and the results of the recent integration/expansion of OHT in primary care in Brazil 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Impacto Ceod (dp) Índice Sic (dp) Livres de cárie (%) No presente estudo verificou-se um aumento do ceod com o aumento da idade, fato confirmado por outros estudos na literatura (TOMITA, 1996;HOFFMANN, 2004;FREIRE, 1999;FEITOSA, 2004;TRAEBERT, 2001;RIHS, 2009;ALMEIDA, 2009;CARVALHO, 2009 (COHEN et al, 2004).…”
unclassified